A Comparative Analysis of the Student Preferences for Digital and Physical Books in Library Usage - Caperida, Cecilia (JPAIR Institutional Research, 2024)
The study investigates student preferences for digital and physical library resources at San Sebastian College-Recoletos de Cavite, Philippines, amidst the evolving landscape of educational technology integration. Through a comprehensive analysis of survey data collected from Senior High School and College students, the research identifies significant trends in resource utilization patterns and their impact on academic achievement. Results indicate a preference for digital resources, although some students still value physical materials. Statistical analyses reveal discipline-specific variations in resource utilization and a positive correlation between the frequency of accessing digital resources and academic performance. The study underscores the importance of aligning library services with student preferences to optimize learning outcomes and foster digital literacy. Recommendations are made for tailored interventions to enhance resource provision and promote equitable access across academic disciplines